The Urgency of Revoking the Voting Rights of Civil Servants to Ensure Neutrality in General and Regional Elections - Wiwin, Wiwin (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This study aims to examine the urgency of revoking the voting rights of civil servants (ASN) as a legal-political solution to address the persistent issue of neutrality violations in general and regional elections in Indonesia. The research employs a normative legal method using a statute approach, conceptual approach, and analytical approach. Legal sources such as the 1945 Constitution, Law No. 20 of 2023 on Civil Servants, and Constitutional Court Decision No. 22/PUU-XII/2014 are analyzed alongside theoretical perspectives, particularly John Rawls’s difference principle, to construct a solid argument for restricting voting rights under certain public service roles. The findings indicate that education, supervision, and law enforcement mechanisms have been largely ineffective in deterring neutrality violations by civil servants. The study argues that the existence of voting rights for ASN creates a conflict of interest that facilitates bureaucratic politicization and transactional politics, especially given that civil service careers are influenced by elected officials through the Civil Service Supervisory Officials (PPK) system. The study concludes that revoking voting rights for civil servants, similar to the policy applied to TNI and POLRI members, is constitutionally justified and effective in promoting impartiality. Legal reform is necessary to amend election laws, restructure PPK appointments, and strengthen merit based systems in civil service management.